ANALYSIS OF THE MAINTENANCE SYSTEM OF WARSHIP BASED ON ISO 9000: 2015 - Novi Shobi Hendri; Abdul Rahman; Adi Bandono; Okol Sri Suharyo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
Today's Organizational Development is intensively carried out by all layers, both Profit and Non-Profit Organizations even in the Military world. The Military World will continue to improve in its Organization because of the demands of the development of the Main Tool system owned. Their Combat Equipment has undergone a lot of renewal and moderation. For this reason, a good Maintenance system effort is based on the ISO 9000: 2015 quality management system. Therefore, an analysis of strengths, weaknesses, opportunities, and obstacles is needed so that a quality management system that is in accordance with existing standards and rules can be developed. The purpose of writing is to formulate a SWOT Analysis integrated with 7 principles of the ISO 9000: 2015 quality management system in Combat Maintenance Maintenance Systems in a country. The research method used is descriptive qualitative, where data is collected through observation and interviews with decision-makers in an organization or company. Keywords: Organizational Benefits, Non Profit, Military, SWOT, ISO 9000: 2015